Razões hematológicas em pacientes com covid-19 internados no Hospital Universitário de Santa Maria - RS - Fernandes, Natieli Flores (2022)
The spread of the SARS-CoV-2 virus, which causes COVID-19, led to a global public health emergency and the declaration of a pandemic by the WHO in 2020. It has been demonstrated laboratory alterations in patients with COVID-19, but the relationship of these parameters with severity, mortality and need for mechanical ventilation is unclear. Therefore, markers that can help in clinical decision-making, such as hematological ratios, are very useful. Thus, this study aimed to describe clinical aspects and analyze the neutrophil/ lymphocyte (NLR), derived neutrophil/ lymphocyte (d-NLR), lymphocyte/ monocyte (LMR), platelet/ lymphocyte (PLR) ratios and the systemic immuno-inflammation index (SII) of hospitalized patients with COVID-19 attended by the Clinical Analysis Laboratory of the University Hospital of Santa Maria - RS between April 1, 2020 and March 31, 2021. This was a retrospective observational analysis of 212 hospitalized COVID-19 patients, who were stratified into a group requiring invasive mechanical ventilation (CNVMI) (n=129), and another group not requiring invasive mechanical ventilation (NVMI) (n =83), also stratified according to mortality outcome, and a control group composed of 198 healthy subjects. From the first complete blood count of each patient performed after admission, NLR, d-NLR, LMR, PLR, NPR, SII were calculated. The NLR, d-NLR, PLR and SII values were higher in the CNVMI group when compared to the other groups (SNVMI and control) (p<0.001). The CNVMI group also showed a lower LMR value and a higher PLR value when compared to the control group. When compared with SNVMI, the CNVMI group showed similar trend behavior (lower LMR and higher PLR) although not statistically significant. From these results, a ROC curve was calculated to verify the sensitivity and specificity of these markers in relation to the need of invasive mechanical ventilation in patients with COVID-19. All parameters, with the exception of the LMR, presented an area greater than 0.5 and the marker with the best response was d-NLR, NLR and NPR which presented areas of 0.735, 0.725 and 0.713, respectively. When the hematological ratios analyzed previously were compared between CNVMI and SNVMI, considering only the non-survivors of each group, no differences were observed (p>0.05). It should be highlighted that these hematological ratios are of low cost for laboratories, since they are obtained from routine complete blood counts. Thus, the analyzed markers showed a high potential for use as auxiliary tool in clinical decisionmaking regarding the need for invasive mechanical ventilation.